2019
DOI: 10.7441/joc.2019.04.10
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Financial Health in the Electrical Engineering Industry

Abstract: One of the characteristics of business competitiveness is business performance. Managerial decision making is one of the main factors that can affect the competitiveness of a company. Financial and economic analysis is an inseparable part of financial management in the practice of business entities. The aim of this contribution is to present several models of forecasting the financial situation of companies. By implementing the Taffler model, Springate model, and the Aspect Global Rating, we assess the financi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 9 publications
0
22
0
1
Order By: Relevance
“…Management, in addition to its bonuses, expects investments in new equipment, technologies or an increase in statutory funds. Thus, managing profits is an opportunity to generate higher revenues at certain costs and thus maximize profits (Stefko et al, 2019). The phenomenon of earnings management has become a crucial research topic in the field of accounting and financial decision-making.…”
mentioning
confidence: 99%
“…Management, in addition to its bonuses, expects investments in new equipment, technologies or an increase in statutory funds. Thus, managing profits is an opportunity to generate higher revenues at certain costs and thus maximize profits (Stefko et al, 2019). The phenomenon of earnings management has become a crucial research topic in the field of accounting and financial decision-making.…”
mentioning
confidence: 99%
“…Oh (2019) analyzed the ecological efficiency of South Korea's state-owned, affiliated and small and medium-sized power generation enterprises by using the method of data envelopment analysis; found that the ecological efficiency of small and medium-sized enterprises, listed companies and subsidiaries of large companies was higher in turn and put forward policy suggestions to encourage and support small and medium-sized enterprises [28]. Stefko et al (2019) studied the financial situation of the whole electrical engineering industry in Slovakia by using the teller model, Springate model and aspect global rating model and analyzed the competitiveness of enterprises to reflect the performance of enterprises [29]. Sellitto et al (2019) used structural equation model to analyze the effectiveness of green strategy, green innovation, green operation externality management and green operation information management on the competition of 70 companies in the electronic and electrical industry in Brazil and found that green strategy and green innovation have a greater impact on the industrial competitiveness [30].…”
Section: Hypothesis 2 (H2)mentioning
confidence: 99%
“…It is an opportunity to have access to branches of banks and other financial institutions, ATMs, self-service terminals, freely to control personal accounts, savings, and the distance to the service unit, trust in financial institutions, operating expenses, document flow. Besides, the works of (Bagmet & Obeid, 2017), (Bakari et al, 2018), (Buriak et al, 2019), (Caplinska & Ohotina, 2019), (Greco, 2017), (Kliestik et al, 2020), (Stefko et al, 2019), (Morscher et al, 2017), (Makarenko & Sirkovska, 2017), (Dave, 2017a;2017b), (Singh, 2018), (García, 2016) consider financial inclusion as an integral part in the development of "healthy" financial society.…”
Section: Literature Reviewmentioning
confidence: 99%